Pengaruh Keberagaman Tenaga Kerja, Kesejahteraan Karyawan dan Tanggung Jawab Sosial terhadap Kinerja ESG (Lembaga Pengembangan Kinerja Dosen, 2025)
This research examines how corporate social responsibility (CSR), employee welfare, and workforce diversity impact an organization's environmental, social, and governance (ESG) performance. In 2023, purposive sampling was used in a quantitative approach to collect data from fifty companies that were listed or unlisted on the Indonesia Stock Exchange (IDX). The results of the multiple linear regression analysis show that workforce diversity, especially with regard to gender, has a favorable and significant impact on ESG performance. Meanwhile, there is a modest boost to employee welfare as well. However, CSR initiatives have a notable detrimental impact on ESG ratings. This research model is able to explain 34.4% of the variation in ESG performance. These findings confirm that internal factors, such as workforce diversity and employee welfare, have a more important role in improving ESG performance compared to CSR that is not implemented strategically.